VARIATIONS OF TRADITIONAL FISH-BASED FOODS TYPICAL OF BANGKA AND BELITUNG: GANGAN AND LEMPAH KUNING - Putri Anggita; Selvi Csintia; Reza; Ardiansyah Kurniawan (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research focuses on discussing typical traditional foods made from fish originating from the islands of Bangka and Belitung. The aim is to find out the differences in the ingredients and the process of making Bangka and Belitung traditional foods, namely Lempah Kuning and Gangan. Lempah kuning is a very famous speciality among the people of Bangka, and Gangan is a speciality food whose main ingredient is made from fish originating from Belitung Island. This research uses a qualitative research type method with data collection methods in the form of observation and also conducting interviews with sources. Lempah Kuning from Bangka and Gangan from Belitung have differences in the types of spices and cooking methods. Lempah Kuning uses Belimbing Wuluh and Gangan utilises the acid from Pineapple. Lempah Kuning uses fish ingredients, while Gangan cooks fish, beef, chicken and duck. The resulting flavours and aromas are different.